ANALISIS PENGARUH PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP BELANJA LANGSUNG PADA PEMERINTAH DAERAH KOTA KENDARI - Mila Sarmila; Wali Aya Rumbia; Muhamad Armawaddin (JEP (Jurnal Ekonomi Pembangunan), 2018)
This study aims to 1) To determine the effect of Regional Original Income (PAD) on the Direct Expenditures of the Regional Government of Kendari City. 2) To find out the effect of the Balancing Fund on the Direct Expenditure of the Regional Government of Kendari City. 3) To find out the effect of Regional Original Income (ROI) and Balancing Funds on Kendari Regional Government Direct Expenditures. The research method used in this research is documentative method and type of descriptive verification research, and data analysis using research data in the form of ROI realization reports, balancing funds, and direct expenditure for 10 periods, namely in the fiscal year 2008-2017 obtained from the Financial Management Service and Regional Assets of Kendari City. The results of the correlation analysis indicate the relationship of local revenue with regional expenditure with a very strong category and the relationship of balancing funds with regional expenditure with a very strong category. The results of partial hypothesis testing can be seen that there is a significant effect of variable local revenue and balancing funds on regional expenditure. Simultaneous hypothesis test results can be seen that there is a significant effect between local revenue and balance funds towards the regional expenditure of Kendari City.